Gender/Nationality Intersections in Attitudes Toward Gun Carry among Israeli Citizens. (February 2022) - Aharoni, Sarai B.; Lewin, Alisa C.; Sa'ar, Amalia
The study explores how nationality and gender effect attitudes on the presence, use, and misuse of guns by security forces and civilians in Israel. Using data from a national survey ( n = 721), we find that Israelis, Jews, and Arabs have more positive attitudes toward military firearms than civilian gun carry. The vast majority agree that display of military arms increases the public sense of security. Numbers are much lower regarding civilian carry. Most respondents, Jews and Arabs, would interfere if witnessed public misuse of firearms. An intersectional analysis finds (1) a gender gap, men have higher odds of reporting a firearm in the household than women; (2) Jews have more positive attitudes toward firearms than Arabs; (3) Jewish men have more positive attitudes toward civilian carry than Jewish women. This gender gap does not appear among Arabs; (4) Jews are more favorable of self-protection as a justification to use arms than Arabs.